Faktor-Faktor Yang Mempengaruhi Kepuasaan Kerja Karyawan PT. Bank Perkreditan Rakyat (BPR) X Koto Singkarak - Wahyu Indah Mursalini (Pustaka Galeri Mandiri, 2021)
This study aims to analyze the factors that influence job satisfaction of employees of PT. Bank Perkreditan Rakyat (BPR) X Koto Singkarak). The sample in this study was 31 respondents based on gender, age, education level, status, and length of service at Rural Bank (BPR) X Koto Singkarak.Based on the results of the analysis that has been carried out, it is obtained that Y = 17.961 -0.157X1 + 0.568X2, which means that the role conflict variable has a negative effect on employee job satisfaction, while the job authority variable positively affects employee job satisfaction. Judging from the results of the R Square of 0.636 or 63.6%. And other factors besides Role Conflict and Work Authority that affect Employee Job Satisfaction by 36.4%. From the results of the t-test analysis obtained |2,182| and 5.217, which means that the role conflict variable affects employee job satisfaction and the job authority variable affects employee job satisfaction. From the results of the F test obtained 24,476 > ftable 2.95, which means that the Conflict of Role and Work Authority on jointly affects Employee Job Satisfaction.